Metaverse integration in higher education curriculum: A systematic literature review - Shafa Dynastia El Amirurrahmah; Faiha Zakha; Nushrotina Bayani (Himpunan Pengembang Kurikulum Indonesia, 2024)
The Metaverse, a fusion of the online and physical worlds, creates an unlimited 3D environment through virtual reality headsets and augmented reality applications. These tools enable users to explore an immersive new reality, free from the physical constraints of the everyday world. This article investigates the transformative potential of the Metaverse in higher education curriculum development using the Systematic Literature Review (SLR) research methodology. Exploring virtual and augmented reality, the research aims to integrate Metaverse technology to enhance curriculum responsiveness seamlessly. The literature review covers various types of Metaverse, emphasizing enriching aspects such as improved learning experiences and global collaboration. Despite facing challenges like initial investments and access disparities, findings indicate a positive impact on curriculum development, facilitating interactive and in-depth learning. Long-term benefits involve career readiness, educational innovation, and paradigm shifts, highlighting the potential of the Metaverse to revolutionize education. This article encourages further exploration and broader-scale implementation of Metaverse in education, both now and in the future. Abstrak Metaverse pada dasarnya adalah gabungan antara dunia online dan fisik, menciptakan lingkungan 3D tanpa batas melalui perangkat seperti headset realitas virtual dan aplikasi realitas tertambah yang memungkinkan pengguna menjelajahi realitas baru yang imersif, bebas dari batasan fisik dunia normal. Artikel ini menyelidiki potensi transformatif Metaverse dalam pengembangan kurikulum pendidikan tinggi dengan metodologi penelitian Systematic Literature Review (SLR). Mengeksplorasi realitas virtual dan realitas tambahan, penelitian bertujuan untuk mengintegrasikan teknologi Metaverse secara mulus guna meningkatkan responsivitas kurikulum. Tinjauan literatur mencakup berbagai jenis Metaverse, menekankan aspek yang memperkaya seperti pengalaman belajar yang ditingkatkan dan kolaborasi global. Meskipun dihadapkan pada tantangan seperti investasi awal dan disparitas akses, temuan menunjukkan dampak positif pada pengembangan kurikulum, memfasilitasi pembelajaran interaktif dan mendalam. Manfaat jangka panjang melibatkan kesiapan karier, inovasi pendidikan, dan perubahan paradigma, menyoroti potensi Metaverse untuk merevolusi pendidikan. Artikel ini mendorong eksplorasi lebih lanjut dan implementasi skala lebih luas mengenai Metaverse dalam dunia pendidikan baik di masa sekarang maupun masa yang akan datang. Kata Kunci: pengembangan kurikulum; pendidikan tinggi; metaverse